A revision of the genus Lepidobrya Womersley (Collembola: Entomobryidae) based on morphology and sequence data of the genotype - Zhang, Feng; Greenslade, Penelope; Stevens, Mark I. (Zootaxa, 2017)
The genus Lepidobrya Womersley, previously placed in Willowsiini, is re-diagnosed based on a redescription of the type species L. mawsoni (Tillyard) and its DNA barcode. Specimens possess narrow, pointed scales on the dens, two inner teeth on unguis, a truncate unguiculus with an outer tooth, a bidentate mucro with a basal spine and ordinary tergal S-chaetae 2, 2|1, 2, 2, ?, 3, so belongs to the Entomobryinae. Its systematic position and relationships to other scaled Entomobryinae genera are discussed and comments are made on the distribution of the genus as well as on ecology.